Effective Realization of Social Partnership and Supply Chain Management in the Russian Federation Economy - Oksana Anatolevna Ignateva; Askar Nailevich Mustafin; Margarita Nikolaevna Maksimova (International Journal of Supply Chain Management, 2019)
Abstract-This article is devoted to studying of social partnership and supply chain strategy from the point of view of its role and value for the economy of the Russian Federation. The group of authors carried out the analysis of the category